Emotional intelligence and performance in a stressful task: The mediating role of self-efficacy. (1st April 2020) - Udayar, Shagini; Fiori, Marina; Bausseron, Elise
Abstract: Emotional intelligence (EI) is argued to predispose individuals to better apprehend and accomplish stressful tasks. Research produced to date has nevertheless mostly neglected the processes that render EI situationally advantageous. In this study, we used path analysis to explore how ability and trait EI relate to delivering a presentation under stress by distinguishing subjective and objective performance. We also proposed self-efficacy as a potential mediator of the trait EI-performance relationship. One hundred and twenty university students completed the STEU, STEM, and GERT (for ability EI) and the TEIQue (for trait EI); then they performed an oral presentation task in front of two evaluators. Students' self-ratings and evaluators' scores composed subjective and objective performance. Results indicated that: (a) self-efficacy fully mediated the relationship between trait EI and both subjective and objective performance; (b) ability EI, in particular emotion understanding (STEU), directly predicted objective performance. These findings highlight one way in which the two leading EI approaches may both contribute to performance under stress, but through distinctive paths.